The application of additive manufacturing technology in pelvic surgery: A bibliometrics analysis - Li, Jian; Wang, Jiani; Lv, Jia; Bai, Junjun; Meng, Shichao; Li, Jinxuan; Wu, Hua (Frontiers in Bioengineering and Biotechnology, 2023)
With the development of material science, additive manufacturing technology has been employed for pelvic surgery, addressing the challenges, such as the complex structure of the pelvis, difficulty in exposing the operative area, and poor visibility, of the traditional pelvic surgery. However, only limited studies have been done to review the research hotspots and trends of the additive manufacturing technology applied for pelvic surgery. In this study, we comprehensively analyzed the literatures related to additive manufacturing technology in pelvic surgery by a bibliometrics analysis and found that additive manufacturing technology is widely used in several aspects of preoperative diagnosis, preoperative planning, intraoperative navigation, and personalized implants for pelvic surgery. Firstly, we searched and screened 856 publications from the Web of Science Core Collection (WoSCC) with TS = (3D printing OR 3D printed OR three-dimensional printing OR additive manufacturing OR rapid prototyping) AND TS = (pelvis OR sacrum OR ilium OR pubis OR ischium OR ischia OR acetabulum OR hip) as the search strategy. Then, 565 of these were eliminated by evaluating the titles and abstracts, leaving 291 pieces of research literature whose relevant information was visually displayed using VOSviewer. Furthermore, 10 publications with high citations were selected by reading all publications extensively for carefully evaluating their Titles, Purposes, Results, Limitations, Journal of affiliation, and Citations. Our results of bibliometric analysis demonstrated that additive manufacturing technology is increasingly applied in pelvic surgery, providing readers with a valuable reference for fully comprehending the research hotspots and trends in the application of additive manufacturing technology in pelvic surgery.